Pemanfaatan Media Digital Berbasis Sastra Lokal dalam Penguatan Literasi Bahasa Inggris dan Identitas Budaya Siswa pada Komunitas Belajar SMAN 1 Pringgasela - Nur Aini, Anisa; M. Afan, M. Afan; Sukardi, Sukardi; Wahidah, Nurul (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2026)
This community service program addresses the limited integration of local cultural context in English literacy activities at the secondary school level, which often results in low student participation and weak cultural relevance in learning. The program focuses on strengthening English literacy and students’ cultural identity through the utilization of digital media based on local literature in the English Learning Community of SMAN 1 Pringgasela. The objective of this program is to improve students’ English literacy skills particularly narrative text comprehension, vocabulary mastery, and speaking confidence while fostering awareness and appreciation of local cultural values. A community-based participatory approach was employed, involving students actively in the planning, implementation, and evaluation of literacy activities. The program stages included needs analysis, development of digital media using local folktales, guided literacy mentoring through video-based storytelling, group discussions, and oral retelling activities, followed by reflective evaluation. Data were collected through observation and descriptive assessment using a simple literacy rubric. The results indicate an improvement in students’ English literacy skills, as reflected in better understanding of narrative texts, increased use of relevant vocabulary, and higher confidence in speaking English. In addition, the program contributed to positive social changes within the learning community, including increased student engagement, more collaborative interactions, the emergence of student leadership, and strengthened cultural awareness. These findings demonstrate that digital local literature can serve as an effective and contextual medium for enhancing English literacy and cultural identity within school-based learning communities.